PENGARUH E-LEARNING TERHADAP RESILIENSI MATEMATIKA SISWA SMP DI MOJOKERTO SELAMA PANDEMI COVID-19 - Hadi Harianto; Andry Isweliyah (MEGA: Jurnal Pendidikan Matematika, 2021)
Pandemic Covid-19 has changed all fields, including the education sector system. Teachers and students are required to learn from home through online learning, this has an effect on student mathematical resilience. This research was motivated by the many findings of decreasing student resilience in mathematics learning. The purpose of this study was to test: (1) Online learning measures by teachers (2) student mathematical resilience during online learning (3) student response to online learning. The method used in this study is descriptive qualitative. The sample consists of 4 math teachers and 6 students with high, medium and low skills from one of the junior high schools in Mojokerto Regency. Data collection techniques use a questionnaire to students to study mathematical resilience students during online learning, interviews to test students' responses to online learning, and interviews and observations with teachers to analyze the steps of online learning. The results showed: 1) Online learning process begins with handouts through Google Classroom, followed by material explanations using zoom meetings and assignments through Google Classroom (2) student resilience to high mathematics during online learning. (3) Students give a positive response to online learning